Isotopically Light Cd in Sediments Underlying Oxygen Deficient Zones - Chen, Lena; Little, Susan H.; Kreissig, Katharina; Severmann, Silke; McManus, James (Frontiers in Earth Science, 2021)
Cadmium is a trace metal of interest in the ocean partly because its concentration mimics that of phosphate. However, deviations from the global mean dissolved Cd/PO4 relationship are present in oxygen deficient zones (ODZs), where Cd is depleted relative to phosphate. This decoupling has been suggested to result from cadmium sulphide (CdS) precipitation in reducing microenvironments within sinking organic matter. We present Cd concentrations and Cd isotope compositions in organic-rich sediments deposited at several upwelling sites along the northeast Pacific continental margin. These sediments all have enriched Cd concentrations relative to crustal material. We calculate a net accumulation rate of Cd in margin settings of between 2.6 to 12.0 × 107 mol/yr, higher than previous estimates, but at the low end of a recently published estimate for the magnitude of the marine sink due to water column CdS precipitation. Cadmium in organic-rich sediments is isotopically light (δ114/110CdNIST-3108 = +0.02 ± 0.14‰, n = 26; 2 SD) compared to deep seawater (+0.3 ± 0.1‰). However, isotope fractionation during diagenesis in continental margin settings appears to be small. Therefore, the light Cd isotope composition of organic-rich sediments is likely to reflect an isotopically light source of Cd. Non-quantitative biological uptake of light Cd by phytoplankton is one possible means of supplying light Cd to the sediment, which would imply that Cd isotopes could be used as a tracer of past ocean productivity. However, water column CdS precipitation is also predicted to preferentially sequester light Cd isotopes from the water column, which could obfuscate Cd as a tracer. We also observe notably light Cd isotope compositions associated with elevated solid phase Fe concentrations, suggesting that scavenging of Cd by Fe oxide phases may contribute to the light Cd isotope composition of sediments. These multiple possible sources of isotopically light Cd to sediments, along with evidence for complex particle cycling of Cd in the water column, bring into question the straightforward application of Cd isotopes as a paleoproductivity proxy.